A low drag suit for ski-cross competitions - Oggiano, L.; Saetran, L. (Procedia Engineering, 2010)
In a ski cross competition, a group of four skiers take simultaneously part of the race and attempt to reach the end of the course. The first two to cross the finish line will advance to the next round. It is then not a timed racing event like the other ski competitions. Since it has been proved that low drag apparels have a major role in sports where high speeds are involved and speeds in ski cross can vary from 50 km/h to 100 km/h (depending on the track), a low drag suit could give an advantage to the athletes. Knowing that it is possible to design suits which are capable to shift the transition from laminar to turbulent regime (giving a great advantage in terms of drag reduction) it has been chosen to use different textiles with different roughness in different parts of the body to minimize the aerodynamic drag. A final suit with a drag reduction of 10% has been designed.